No evidence for human papillomavirus infection in focal cortical dysplasia IIb - Coras, Roland; Korn, Klaus; Bien, Christian G.; Kalbhenn, Thilo; Roessler, Karl; Kobow, Katja; Giedl, Josef; Fleckenstein, Bernhard; Blümcke, Ingmar (Annals of Neurology, 2015)
The etiology of focal cortical dysplasia type IIb (FCDIIb) remains enigmatic in patients suffering from drug-resistant epilepsy, and an aberrant activation of the mammalian target of rapamycin complex 1 signaling pathway (mTORC1) was detected in this developmental brain malformation. Recently, the human papillomavirus (HPV) oncoprotein E6 has been identified as a potent activator of mTORC1, and HPV16 E6 has been described to persist in balloon cells obtained from surgical FCDIIb specimens. Although this observation was replicated by an independent second report, it contradicts current knowledge of HPV biology. HPV infects the squamous or mucocutaneous epithelium; hematogenic spread into other tissues has not been observed. In addition, brain carcinogenesis has never been reported in FCDIIb patients. Herein, we have tried to confirm 2 previous reports of HPV16 E6 infection using an independent series of 14 surgical specimens with histopathologically confirmed FCDIIb.Snap-frozen FCDIIb specimens were tested for HPV DNA using the primer set for amplification of the complete E6 reading frame of HPV16 and 3 other sets of primers (2 consensus primer sets detecting multiple HPV genotypes, and another primer set specifically used for HPV16). Furthermore, formalin-fixed and paraffin-embedded histopathological preparations were immunohistochemically analyzed using previously described antibodies directed against the HPV E6 oncoprotein.All 14 FCDIIb specimens were negative for HPV DNA with all 4 primer sets. Antibodies directed against the HPV E6 epitope showed weak labeling of cytoplasm in balloon cells, as previously described in FCDIIb, but also in other cell populations.Our data did not confirm previously reported evidence for HPV16 detection in FCDIIb. Ann Neurol 2015;77:312-319.
EVALuna2:6690